Association of change in daily step count over five years with insulin sensitivity and adiposity: population based cohort study. (13th January 2011) - Dwyer, T; Ponsonby, A-L; Ukoumunne, O C; Pezic, A; Venn, A; Dunstan, D; Barr, E; Blair, S; Cochrane, J; Zimmet, P; Shaw, J
Abstract : Objectives To investigate the association between change in daily step count and both adiposity and insulin sensitivity and the extent to which the association between change in daily step count and insulin sensitivity may be mediated by adiposity. Design Population based cohort study. Setting Tasmania, Australia. Participants 592 adults (men (n=267), mean age 51.4 (SD 12.2) years; women (n=325), mean age 50.3 (12.3) years) who participated in the Tasmanian component of the national AusDiab Study in 2000 and 2005. Main outcome measures Body mass index, waist to hip ratio, and HOMA insulin sensitivity at follow-up in 2005. Results Over the five year period, the daily step count decreased for 65% (n=382) of participants. Having a higher daily step count in 2005 than in 2000 was independently associated with lower body mass index (0.08 (95% confidence interval 0.04 to 0.12) lower per 1000 steps), lower waist to hip ratio (0.15 (0.07 to 0.23) lower), and greater insulin sensitivity (1.38 (0.14 to 2.63) HOMA units higher) in 2005. The mean increase in HOMA units fell to 0.34 (−0.79 to 1.47) after adjustment for body mass index in 2005. Conclusions Among community dwelling, middle aged adults, a higher daily step count at five year follow-up than at baseline was associated with better insulin sensitivity. This effect seems to be largely mediated through lower adiposity.